Distributional dynamics under smoothly state-dependent pricing - James Costain; Anton Nakov (European Central Bank (ECB), 2011)
Starting from the assumption that firms are more likely to adjust their prices when doing so is more valuable, this paper analyzes monetary policy shocks in a DSGE model with firm-level heterogeneity. The model is calibrated to retail price microdata, and inflation responses are decomposed into “intensive”, “extensive”, and “selection” margins. Money growth and Taylor rule shocks both have nontrivial real effects, because the low state dependence implied by the data rules out the strong selection effect associated with fixed menu costs. The response to firm-specific shocks is gradual, though inappropriate econometrics might make it appear immediate.
Keywords: E31; E52; D81; 330; heterogeneity; menu costs; nominal rigidity; state-dependent pricing; Taylor rule; Taylor-Regel; Dynamisches Gleichgewicht; Preismanagement; Preisrigidität; Theorie